2010
DOI: 10.5229/jecst.2010.1.2.075
|View full text |Cite
|
Sign up to set email alerts
|

Improved Tri-iodide Reduction Reaction of Co-TMPP/C as a Non-Pt Counter Electrode in Dye-Sensitized Solar Cells

Abstract: :We report Co-tetramethoxyphenylporphyrin on carbon particles (Co-TMPP/C) as a non-Pt catalyst for tri-iodide reduction in dye-sensitized solar cells (DSSCs). The presence of well-dispersed carbon and cobalt source in the catalyst surface is confirmed by transmission electron microscopy, scanning electron microscopy, and energy dispersive X-ray analysis. In the C 1s, Co 2p, and N 1s peaks measured by X-ray photoelectron spectroscopy, the C-N, Co-N 4 , and N-C are assigned to the component at 285.7, 781.8, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…[35] For 7.5 % CoO x @Co-NC shown in Figure 4d, two fitted peaks for Co 2p 3/2 were Co 3 + (780.6 eV) and Co-N 4 (781.8 eV), respectively. [4,23,36,37] The deconvoluted peaks in O 1s spectrum of 7.5 % CoO x @Co-NC located at 530.8 eV, 531.6 eV and 532.9 eV were associated to O bound to Co (Co-O), hydroxyl species or surface adsorbed O molecules (O OH À /O2 ) and adsorbed molecular water (O H2O ), respectively. [38] The appearance of Co-N 4 , Co 3 + and Co-O species in the XPS spectrums of 7.5 % CoO x @Co-NC indicated that the Co-N 4 macrocycles and CoO x nanoclusters were successfully formed after the direct thermal treatment of Co-OCN.…”
Section: Performance and Compositionmentioning
confidence: 99%
“…[35] For 7.5 % CoO x @Co-NC shown in Figure 4d, two fitted peaks for Co 2p 3/2 were Co 3 + (780.6 eV) and Co-N 4 (781.8 eV), respectively. [4,23,36,37] The deconvoluted peaks in O 1s spectrum of 7.5 % CoO x @Co-NC located at 530.8 eV, 531.6 eV and 532.9 eV were associated to O bound to Co (Co-O), hydroxyl species or surface adsorbed O molecules (O OH À /O2 ) and adsorbed molecular water (O H2O ), respectively. [38] The appearance of Co-N 4 , Co 3 + and Co-O species in the XPS spectrums of 7.5 % CoO x @Co-NC indicated that the Co-N 4 macrocycles and CoO x nanoclusters were successfully formed after the direct thermal treatment of Co-OCN.…”
Section: Performance and Compositionmentioning
confidence: 99%